2011
DOI: 10.1186/1471-2180-11-159
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of Stenotrophomonas maltophiliaisolates from patients with cystic fibrosis: Genome diversity, biofilm formation, and virulence

Abstract: BackgroundStenotrophomonas maltophilia is emerging as one of the most frequently found bacteria in cystic fibrosis (CF) patients. In the present study, phenotypic and genotypic traits of a set of 98 isolates of S. maltophilia obtained from clinical (CF and non-CF patients) and environmental sources were comparatively evaluated.ResultsS. maltophilia exhibited a high level of genomic diversity in both CF and non-CF group, thus possibly allowing this bacterium to expand its pathogenic potentials. Strains sharing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 58 publications
7
116
3
2
Order By: Relevance
“…Our results revealed that rmlA, spgM, rpfF genes in S. maltophilia which are responsible for biofilm formation showed 100% occurrence in all isolates which are moderately adherent and strongly adherent, these results shows little difference than that presented by Pompilio et al which showed an overall prevalence of 65.2, 88.8 and 61.8%, respectively [14]. This difference may come from the genetic diversity of MDR S. maltophilia isolates between Egyptian and overseas hospitals worldwide.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…Our results revealed that rmlA, spgM, rpfF genes in S. maltophilia which are responsible for biofilm formation showed 100% occurrence in all isolates which are moderately adherent and strongly adherent, these results shows little difference than that presented by Pompilio et al which showed an overall prevalence of 65.2, 88.8 and 61.8%, respectively [14]. This difference may come from the genetic diversity of MDR S. maltophilia isolates between Egyptian and overseas hospitals worldwide.…”
Section: Resultscontrasting
confidence: 56%
“…Detection of rmlA, spgM, rpfF genes in S. maltophilia which are responsible for biofilm formation [14]: Fifty isolates were tested for the presence of rmlA, spgM, rpfF genes that are responsible for their abilities to produce biofilm using PCR. 49, 50 and 50 Isolates showed positive results to the three genes respectively by showing a band on 82 bp, 80 bp and 151 bp, respectively as illustrated in Figures 6-8.…”
Section: Detection Of Biofilm Formation Of Bioadherent Isolates By Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms are a community of microbial organisms (either one or multiple species of bacteria) that inhabit a favorable growing environment such as an extracellular mucus (in the case of biofilms for cystic fibrosis patients) but also including nonorganic environments such as rocks (3) . The exact mechanism that facilitates biofilm creation and adhesion is not well understood for most species (5) . However, it is understood that the physical structure of the biofilm (which often exists as an extracellular matrix or slime layer secreted by the organisms) creates an environment that is both ideal for bacterial growth and adaptation while simultaneously severely hindering the effectiveness of antibiotic treatment (3) .…”
Section: Stenotrophomonas Maltophilia Pseudomonas Aeruginosa Staphymentioning
confidence: 99%
“…Although the specific nature of the effectors resulting in synergism between bacteria that makes the multi-species biofilms so robust are not fully understood, intercellular signaling is expected to be involved (5,7) . Quorum sensing could play a role, as it is known to play an important role in the virulence of P. aeruginosa (14) P. aeruginosa uses three different types of signaling systems (for quorum sensing) to communicate with itself as well as other species.…”
Section: Stenotrophomonas Maltophilia Pseudomonas Aeruginosa Staphymentioning
confidence: 99%